2015
DOI: 10.1111/jop.12396
|View full text |Cite
|
Sign up to set email alerts
|

ALK1 expression in oral lichen planus: a possible relation to microvessel density

Abstract: ALK1 expression and MVD are increased in OLP, particularly in A/ELP type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(26 citation statements)
references
References 40 publications
1
24
1
Order By: Relevance
“…Additionally, MVD in OLP tissue increased with the deterioration of the lesion. Previous results, together with those from the present study, indicated that increased angiogenesis may serve a vital role in the malignant transformation of OLP (29,30). However, the mechanism underlying this phenomenon remains unclear.…”
Section: Discussionsupporting
confidence: 66%
“…Additionally, MVD in OLP tissue increased with the deterioration of the lesion. Previous results, together with those from the present study, indicated that increased angiogenesis may serve a vital role in the malignant transformation of OLP (29,30). However, the mechanism underlying this phenomenon remains unclear.…”
Section: Discussionsupporting
confidence: 66%
“…[ 16 ] and Hazzaa et al . [ 32 ] These observations suggested that angiogenesis is one of the key contributing factors in the progression of OLP.…”
Section: Discussionmentioning
confidence: 99%
“…endothelial growth factor correlated closely with the different clinical forms of OLP regions [13,37,38]. Mittal, et al suggested that angiogenesis was significantly increased in OLP as compared to normal oral mucosa, and also in erosive OLP as compared to reticular OLP; this suggests angiogenesis as a main contributing factor in the progression of OLP [13].…”
Section: Evaluation Of Average Areas and Ipcl Anglesmentioning
confidence: 92%